(untitled) (Bioresearch Communications, 2024)
Background: High population density makes Bangladesh more vulnerable to a pandemic situation like COVID-19. It is evident from the scientific literature that proper nutritional practices might be effective in preventing various infections. The objective of this research work was to explore the nutritional as well as lifestyle practices among the urban-rural residents of Jashore district and to assess the association of those practices with their residential settings. Methods: It was a cross-sectional study where about 134 respondents (18-50 years) were selected by convenience sampling method from eight rural and seven urban areas of Jashore district in Bangladesh. Association between residence type and various concerned practices have been explored by Pearson chi-square test, binary and multinomial logistic regression analysis. Results: It was found from the results of binary and multinomial logistic regression that, the intake of vitamin D rich foods (OR: 3.45; 95% CI: 1.48,8.07), folic acid rich foods (OR:0.20; 95% CI:0.09,0.46), vitamin B12 rich foods (OR:0.11; 95% CI:0.02,0.52), iron rich foods (OR:0.23; 95% CI:0.08,0.66), and melatonin rich foods (OR:0.15; 95% CI:0.05,0.40) were significantly associated (P<.05) with residential area (urban and rural) of the respondents. On the other hand, no association was found (P>.05) between other immune-boosting nutrient-rich foods such as complex carbohydrates, polyunsaturated fatty acid, vitamin A, vitamin E, vitamin C, Pyridoxine, zinc and selenium rich foods and respondents’ residential area. Moroever, the association was not observed (P>.05) in case of supplement intake of various immune boosting nutrients and area. Among the lifestyle practices, no significant association was found regarding sleep patterns among the respondents but various daily physical movements (OR: 0.19; 95% CI:0.07,0.48) were found higher among the rural respondents. Conclusion: Daily intake of vitamin D rich foods was found higher among the urban respondents but daily intake of folic acid, vitamin B12, iron and melatonin rich foods were found higher among the rural residents. It was also observed that the physical activities were better maintained among the rural respondents than their urban counterparts. Bioresearch Commu. 10(2): 1545-1552, 2024 (July)